Cultural Dimensions of Symbols Style and Power Artifactual Communication in Abdul Muhaimin Iskandar Declaration Video - Maskuri, M. Ibnu Naufal; Daulay, Hamdan; Rifa'i, Akhmad; Ridho, Ali; Tahrus, Zainun Nur Hisyam (Fakultas Ilmu Budaya, Universitas Jambi, 2026)
Abdul Muhaimin Iskandar is a national political figure facing image challenges due to several controversies, such as the